Prognostic significance of circulating Epstein‐Barr virus DNA in pulmonary lymphoepithelioma‐like carcinoma: A meta‐analysis and validation study. Issue 1 (8th December 2022) - Wei, Xinyan; Wei, Zuyou; Zheng, Guixian; Xie, Ting; Huo, Zengyu; Huang, Yanbing; Chen, Xiaoli; Bai, Jing
Abstract: In small‐scale studies, circulating Epstein‐Barr virus (EBV) DNA levels have prognostic value in patients with pulmonary lymphoepithelioma‐like carcinoma (LELC). Therefore, we performed a comprehensive meta‐analysis to evaluate the prognostic significance of circulating EBV DNA levels in patients with pulmonary LELC. Studies that discussed the prognostic significance of circulating EBV DNA detection in pulmonary LELC were eligible for inclusion in this study. The overall survival (OS) and progression‐free survival (PFS) were the primary outcomes. Pooled hazard ratio (HR), 95% confidence intervals (CIs), and p value were calculated to estimate the prognostic significance of EBV DNA levels. Additionally, we conducted a further observation using an independent cohort. The pooled HR and 95% CI of pretreatment EBV DNA levels for OS and PFS were 3.63 (95% CI: 2.90–4.55) and 2.88 (95% CI: 1.90–4.38), respectively. The pooled HR and 95% CI for Posttreatment EBV DNA levels for OS and PFS were 3.77 (95% CI: 2.96–4.80) and 3.52 (95% CI: 1.91–6.51, p < 0.001), respectively. The independent cohort showed similar results that patients with high pretreatment EBV DNA or positive posttreatment EBV DNA had significantly inferior PFS. Circulating EBV DNA levels provide prognostic values of survival and treatment response in pulmonary LELC patients.